Tinjauan Ulang Living Hadis dan Living Sunnah: Pemaknaan dan Eksistensi - Nuzuliyah, Wilda Rahmatin (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2022)
This article aims to review the meaning of living hadith and living sunnah as explained by M. Khairil Anwar in the article